If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 5c + -3 = 5x + -1(x + 2) + -1 Reorder the terms: -3 + 5c = 5x + -1(x + 2) + -1 Reorder the terms: -3 + 5c = 5x + -1(2 + x) + -1 -3 + 5c = 5x + (2 * -1 + x * -1) + -1 -3 + 5c = 5x + (-2 + -1x) + -1 Reorder the terms: -3 + 5c = -2 + -1 + 5x + -1x Combine like terms: -2 + -1 = -3 -3 + 5c = -3 + 5x + -1x Combine like terms: 5x + -1x = 4x -3 + 5c = -3 + 4x Add '3' to each side of the equation. -3 + 3 + 5c = -3 + 3 + 4x Combine like terms: -3 + 3 = 0 0 + 5c = -3 + 3 + 4x 5c = -3 + 3 + 4x Combine like terms: -3 + 3 = 0 5c = 0 + 4x 5c = 4x Solving 5c = 4x Solving for variable 'c'. Move all terms containing c to the left, all other terms to the right. Divide each side by '5'. c = 0.8x Simplifying c = 0.8x
| N=0.5s+-1z | | 7-1/2x=-4 | | 8x-75=5x-12 | | 5x-18=y | | 5y^2-13y-28= | | 1x-1=5x-4x-4+25 | | -99/x=2 | | 3x+19=56 | | V=(24-2x)(18-2x)x | | -3x+14=-7 | | 9x+7y=19.7 | | 6r^4/r^7 | | 2e^3x-1=e^2x+1 | | 3(3x+5y)-9x-7y=3(19.825)-19.7 | | 2x(x-3)=8(x-3) | | X^8/x^9 | | -8-3=10x+3-9x | | 11x-9y-10= | | a*3+5=12 | | 4x(3x^3y^4)= | | I=F-IR | | 2x^2-20x-48= | | 5x+6x-3=21 | | F-IR=I | | 7/9-3/18 | | F=i+ir | | x^2+3x-2012=0 | | (w)(w+7)=0 | | x-18sqrtx+80=0 | | I=f-1ir | | (4x^2-x)= | | (y-5)2=100 |